Status and Potential of Lithium Niobate on Insulator (LNOI) for Photonic Integrated Circuits. Issue 4 (23rd February 2018) - Boes, Andreas; Corcoran, Bill; Chang, Lin; Bowers, John; Mitchell, Arnan
Abstract: Lithium niobate on insulator (LNOI) technology is revolutionizing the lithium niobate industry, enabling higher performance, lower cost and entirely new devices and applications. The availability of LNOI wafers has sparked significant interest in the platform for integrated optical applications, as LNOI offers the attractive material properties of lithium niobate, while also offering the stronger optical confinement and a high optical element integration density that has driven the success of more mature silicon and silicon nitride (SiN) photonics platforms. Due to some similarities between LNOI and SiN, established techniques and standards can readily be adapted to the LNOI platform including a significant array of interface approaches, device designs and also heterogeneous integration techniques for laser sources and photodetectors. In this contribution, we review the latest developments in this platform, examine where further development is necessary to achieve more functionalities in LNOI integrated optical circuits and make a few suggestions of interesting applications that could be realized in this platform. Abstract : Lithium niobate on insulator (LNOI) technology is revolutionizing the lithium niobate industry, enabling higher performance, lower cost and entirely new devices and applications. In this contribution, we review the latest developments in this platform, examine where further development is necessary to achieve more functionalities in LNOI integrated optical circuits, and identify potential future applications.